KAJIAN KONSERVASI MANGROVE DI PESISIR PANTAI SUMATERA BARAT - Anita Anita; Neneng Marlian; Nabil Zurba (Journal of Aceh Aquatic Sciences, 2022)
The mangrove forest of West Sumatra, was damaged about one kilometer of mangrove forest in a protected area in Apar Village, Pariaman City, West Sumatra, was damaged. This destruction was the result of the project to open a road connecting Ampalu Village to Padang Birikbirik, North Pariaman District. Data collection was carried out at the Technical Implementation Unit of the Marine and Fisheries Resources Conservation Service (KPSDKP) of North Sumatra Province, on January 10 to February 10, 2020, field data collection was carried out for 1 month. The method used in data collection is using the Observation method, which is systematic observation and recording of the symptoms studied. Mangroves that are conserved by UPTD KPSDKP Pariaman are Rhizopora sp, Nipah, Avecenia, and more dominated by Rhizopora sp. The community continued to cut down the mangroves and eventually the mangroves in Apar Village became extinct, so ideas emerged from the Apar Village community to restore the preservation of the mangrove forest by means of conservation or rehabilitation. Mangrove conservation techniques at UPTD KPSDKP include: Preparation of planting sites, preparation of tools, taking seeds, mangrove nurseries, planting mangrove seedlings, measuring mangrove growth, monitoring and measuring mangrove water quality once a week.